Advances in Irradiated Livestock Vaccine Research and Production Addressing the Unmet Needs for Farmers and Veterinary Services in FAO/IAEA Member States - Unger, Hermann; Kangethe, Richard T.; Liaqat, Fatima; Viljoen, Gerrit J. (Frontiers in Immunology, 2022)
The Animal Production and Health section (APH) of the Joint FAO/IAEA Centre of Nuclear Techniques in Food and Agriculture at the International Atomic Energy Agency has over the last 58 years provided technical and scientific support to more than 100 countries through coordinated research activities and technical co-operation projects in peaceful uses of nuclear technologies. A key component of this support has been the development of irradiated vaccines targeting diseases that are endemic to participating countries. APH laboratories has over the last decade developed new techniques and has put in place a framework that allows researchers from participating member states to develop relevant vaccines targeting local diseases using irradiation as a tool for improving livestock resources.